Scooby-Doo meets the Boo Brothers [videorecording (DVD)] - Messick, Don; Kasem, Casey; Booke, Sorrell, 1930-1994; Carroll, Victoria (Herman, Gail, 1959-, 2003)
Shaggy's uncle leaves him a fortune in hidden jewels, but why is his uncle's ghost chasing after Scooby and the gang? Is it really a ghost? Watch how the Boo Brothers, a phantom family of ghoul chasing ghosts, help the gang unravel this spooky mystery.